Defining stressor clinical activities from nursing students perception - Maryam Alikhani; Farangis Shahpourian; Fateme Maboodian; Parviz Kamali (Iran University of Medical Sciences, 1988)
What are you studying is derived from a descriptive study on 195 nursing students in second, third and four years of bachelorette degree in nursing. A questionnaire complained of 93 questions was used. Each of the questions defined one of basic and essential nursing experiences. This experiences categorized in 4 groups: physical patient care, interpersonal relationships with patients and their families, relationships with medical and educational personal in clinical practice and environmental relationships. All the research samples received the questionnaire in one stage.   Findings showed that kind of clinical stressor experiences are different between students in different years of nursing education. Students in higher years had lesser clinical stressors experiences. In other words years of education has an impact on students' personal perceptions of nursing stressor experiences.